Precedents without precedent: substantially equal cases as causal of rejection of the resources of constitutional remedy - Cruces Burga, Alberto (2017)
There are several judgments of the Constitutional Court that have marked important precedents.These precedents contain a normative element, which determines the jurisdictional action in a great number of future acses.In this article, the author develops how the judgment of the case Vásquez Romero has set a precedent of great importance regarding access to the Constitutional Court. The author will analyze the impact of this precedent on the grounds for rejection of the constitutional grievance remedies as they are substantially equal cases.